Peran Konseling Karir dalam Kesiapan Kerja Siswa Madrasah Aliyah Negeri di Kota Sungai Penuh - Aini, Hidayati; Pratama, Farhan Fajar; Gisnando, Gipa (Ma'soem University, 2025)
Career counseling plays a crucial role in preparing young generations for a dynamic workforce. This study aims to analyze the role of career counseling services at public Islamic high schools (Madrasah Aliyah Negeri 1 and 2) in Sungai Penuh City in preparing students for the world of work. A qualitative approach with a multi-site study design was employed. Data were collected through semi-structured interviews with 10 final-year students and 2 guidance and counseling teachers, as well as participatory observations, followed by thematic analysis. The results indicate that career counseling consistently contributes to enhancing students’ self-awareness, career planning, and soft skills development. This process helps students align personal interests and spiritual values with career opportunities. These findings support career development theories and provide a practical basis for strengthening counseling services in schools with a religious background. In conclusion, career counseling services need to be optimized with a personalized and integrated approach. Further research is recommended to explore the quantitative impact of these services